2008
DOI: 10.1021/jp077180k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Ethyne and But-2-yne. 2. Master Equation Simulations

Abstract: The aim of this study is to improve understanding of the tropospheric oxidation of ethyne (acetylene, C2H2) and but-2-yne, which takes place in the presence of HO and O2. The details of the potential energy hypersurface have been discussed in a previous article [Maranzana et al., J. Phys. Chem. A 2008, 112, XXXX]. For both molecules, the initial addition of HO radical to the triple bond is followed by addition of O2 to form peroxyl radicals. In both reaction systems, the peroxyl radicals take two isomeric form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The lowest-energy route available to T1 involves isomerisation via TS1c(T) to give Int1c(T), a three-membered ring, which then dissociates via TS2c(T) to give HCOOH + HCO. Maranzana et al [25] carried out master equation calculations on this reaction which gave product yields in good agreement with experiment.…”
Section: H 2 + Oh + Omentioning
confidence: 67%
“…The lowest-energy route available to T1 involves isomerisation via TS1c(T) to give Int1c(T), a three-membered ring, which then dissociates via TS2c(T) to give HCOOH + HCO. Maranzana et al [25] carried out master equation calculations on this reaction which gave product yields in good agreement with experiment.…”
Section: H 2 + Oh + Omentioning
confidence: 67%
“…This demonstrates that the formation of products occurs directly from the peroxy radical. The finding that HOCHCHOO is shortlived and leads to regeneration of the OH radical has been confirmed in a number of experimental and theoretical studies .…”
Section: Detailed Kinetic Modelmentioning
confidence: 74%
“…However, the fast reaction with O 2 is the major consumption step, even at higher temperatures. Alzueta et al identified the chain‐propagating sequencetruerightC2H2+ OH C2H2 OH +O2 OCHCHO + OH as important for the onset of reaction for C 2 H 2 at atmospheric pressure and temperatures above 700 K. Interest in this oxidation pathway for atmospheric chemistry has spawned a range of experimental and theoretical studies on the C 2 H 2 + OH + O 2 reaction at low temperature . Hatakeyama et al showed in smoke‐chamber experiments that the reaction generates glyoxal and formic acid,trueright CHCHOH +O2 OCHCHO + OH trueright CHCHOH +O2 HOCHO + HCO …”
Section: Detailed Kinetic Modelmentioning
confidence: 99%
“…Therefore, despite impressive advances in the accuracy of DFT methodologies accomplished during the last few years, 22 discrepancies between experimentally measured and theoretically predicted rate constants are unavoidable. This important point that have been recently stressed by several authors in different contexts, 47,[54][55][56] should be kept in mind when assessing the output of kinetics theoretical predictions.…”
Section: -mentioning
confidence: 99%